Investigating the CYP2E1 Potential Role in the Mechanisms Behind INH/LPS-Induced Hepatotoxicity - Hozeifa M. Hassan; Hozeifa M. Hassan; Bashir A. Yousef; Bashir A. Yousef; Hongli Guo; Liu Xiaoxin; Luyong Zhang; Luyong Zhang; Luyong Zhang; Zhenzhou Jiang; Zhenzhou Jiang (Frontiers Media S.A., 2018)
Tuberculosis (TB) is one of the oldest infectious diseases that affected humankind and remains one of the world's deadliest communicable diseases that could be considered as global emergency, but the discovery and development of isoniazid (INH) in the 1950s paved the way to an effective single and/or combined first-line anti-TB therapy. However, administration of INH induces severe hepatic toxicity in some patients. Previously, we establish a rat model of INH hepatotoxicity utilizing the inflammatory stress theory, in which bacterial lipopolysaccharide (LPS) potentially enhanced INH toxicity. These enhancing activities ranged between augmenting the inflammatory stress, oxidative stress, alteration of bile acid homeostasis, and CYP2E1 over-expression. Although pre-treatment with dexamethasone (DEX) helped overcome both inflammatory and oxidative stress which ended-up in alleviation of LPS augmenting effects, but still minor toxicities were being detected, alongside with CYP2E1 over expression. This finding positively indicated the corner-stone role played by CYP2E1 in the pathogenesis of INH/LPS-induced liver damage. Therefore, we examined whether INH/LPS co-treatment with CYP2E1 inhibitor diallyl sulfide (DAS) and DEX can protect against the INH/LPS-induced hepatotoxicity. Our results showed that pre-administration of both DAS and DEX caused significant reduction in serum TBA, TBil, and gamma-glutamyl transferase levels. Furthermore, the histopathological analysis showed that DAS and DEX could effectively reverse the liver lesions seen following INH/LPS treatment and protect against hepatic steatosis as indicated by absence of lipid accumulation. Pre-treatment with DAS alone could not completely block the CYP2E1 protein expression following INH/LPS treatment, as appeared in the immunoblotting and immunohistochemistry results. This is probably due to the fact that the combined enhancement activities of both INH and LPS on CYP2E1 protein expression levels might resist the blocking probabilities of DAS. In the meantime, addition of DEX to the DAS/INH/LPS combination caused a significant reduction in CYP2E1 protein expression as revealed by the immunoblotting and fading coloration in immunohistochemistry results. Thus, addition of DEX and DAS together caused strong protection against INH/LPS-induced hepatic damage. These findings reveal the potential therapeutic value of combining DAS and DEX with INH in TB management for reducing the potential risk and incidences of hepatotoxicity.